Description of deutonymphs of Kamertonia polonica Gabryś, 2000 (Acari: Actinotrichida: Erythraeidae) - Roland, Elżbieta; Gabryś, Grzegorz (Biological Letters, 2014)
A detailed description of deutonymphs of Kamertonia polonica Gabryś, 2000 is provided for the first time. Their general appearance is similar to adults and the slight differences are quantitative. The distribution of K. polonica is discussed.